2021
DOI: 10.3390/jcm10163587
|View full text |Cite
|
Sign up to set email alerts
|

Failure of High-Flow Nasal Cannula Therapy in Pneumonia and Non-Pneumonia Sepsis Patients: A Prospective Cohort Study

Abstract: Despite the increasing use of high-flow nasal cannulas (HFNCs) to treat critically ill patients, data on their effectiveness for sepsis patients remains very limited. We studied a prospective cohort of sepsis patients from the Korean Sepsis Registry (18 intensive care units (ICUs)). Patients started on HFNC therapy for hypoxemia within the first three ICU days were enrolled. HFNC failure was defined as intubation or ICU death, and the primary outcome was early HFNC failure occurring within 72 h of HFNC initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Therefore, patients with lower oxygenation index also had a higher risk of failure in HFNO. Previous studies on the prognosis of pulmonary infection induced sepsis showed that oxygenation index was an independent risk factor for predicting in-hospital mortality 31 , 32 . The results of Liu et al 33 also confirmed that oxygenation index was an independent risk factor for patients with non-invasive ventilation failure.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, patients with lower oxygenation index also had a higher risk of failure in HFNO. Previous studies on the prognosis of pulmonary infection induced sepsis showed that oxygenation index was an independent risk factor for predicting in-hospital mortality 31 , 32 . The results of Liu et al 33 also confirmed that oxygenation index was an independent risk factor for patients with non-invasive ventilation failure.…”
Section: Discussionmentioning
confidence: 96%
“…Recent data support the use of an HFNC in this subset, especially during weaning phases from mechanical ventilation or when preventing reintubation [162,163]. However, Kim et al emphasized the need for close patient monitoring since an HNFC may fail to prevent intubation or increase survival rates [164].…”
Section: High-flow Nasal Cannulamentioning
confidence: 99%